Training civil servants in the administration of Central and Eastern Europe a missed opportunity. - Balducci, Massimo (1995)
The European Union, Western European Countries, the United States, Canada and Japan are currently investing considerable sums in training of civil servants for Central and Eastern European countries. The training have two objectives: first, it can be a means of transmitting known and accepted knowledge, techniques and values; second, it can be used to modify accepted knowledge and values. In the first instance, training is an important tool for maintaining order and, in the second, training represents an instrument for change
Keywords: Bureaucracy - Training of - Europe; Civil service - Training of - Europe; Civil service - Europe